A study of the monsoon depression intensifying into cyclonic storm over land (MAUSAM, 1977)
The monsoon depression which formed over the head of the Bay of Bengal and neighbourhood on 8 September 1970 and crossed West Bengal coast near Contai on the evening of 9th, showed some unusual features. It progressively intensified into a cyclonic storm over the land although its development was rather slow. Further, it executed a loop around Kanpur. This system caused very heavy rainfall along its track, particularly over the southern parts of Uttar Pradesh. A study of this depression with the help of weather satellite cloud pictures has been presented in this paper.